2007
DOI: 10.1007/s11517-007-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival in critical patients by use of body temperature regularity measurement based on approximate entropy

Abstract: Body temperature is a classical diagnostic tool for a number of diseases. However, it is usually employed as a plain binary classification function (febrile or not febrile), and therefore its diagnostic power has not been fully developed. In this paper we describe how body temperature regularity can be used for diagnosis. Our proposed methodology is based on obtaining accurate long-term temperature recordings at high sampling frequencies and analyzing the temperature signal using a regularity metric (approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…However, our study consisted of visual assessment of relatively infrequent temperature measurements. Furthermore, previous investigations of body temperature variability focused on predicting disease severity in patients with existing multiple organ failure [31,32] or in patients who were already suspected of being infected [33]. None of the patients in our study, however, were clinically suspected of being septic during the time period of the temperature measurements.…”
Section: Discussionmentioning
confidence: 86%
“…However, our study consisted of visual assessment of relatively infrequent temperature measurements. Furthermore, previous investigations of body temperature variability focused on predicting disease severity in patients with existing multiple organ failure [31,32] or in patients who were already suspected of being infected [33]. None of the patients in our study, however, were clinically suspected of being septic during the time period of the temperature measurements.…”
Section: Discussionmentioning
confidence: 86%
“…These signal complexity calculations contribute to capture the dynamic aspects of temperature regulation. Some results in this regard have already been published, see [12]. …”
Section: Device Descriptionmentioning
confidence: 99%
“…New analytical techniques derived from complex time-series analysis (approximate entropy [6, 7], sample entropy [8], Lempel Ziv algorithm [9, 10], detrended fluctuation analysis [11]) have been shown useful to study and classify temperature, even in the absence of fever. For instance, it has been shown that there is a good correlation between physiological status and ApEn of the temperature profile in critically ill patients, and that ApEn is a prognostic marker as good as conventional scoring systems, with the advantage of being non-invasive and a continuous, rather than episodic, evaluation [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using body temperature entropy estimation, in a similar way as in Sec.3.2, we found a correlation between a patient condition, and their body temperature regularity [18,19]. There was a statistically significant difference between the regularity of signals from patients that survived and patients that did not (72% classifier accuracy).…”
Section: Predicting Survival In Critical Patientsmentioning
confidence: 54%